Financial management of young families within the framework of Islamic methodology - Wahidin Wahidin (International Forum of Researchers and Lecturers, 2023)
The focus of this research is on the significance of prudent financial management in the context of Islamic consumption. Young families face complex financial challenges, and understanding the principles of Islam in financial management can provide a solid foundation for both financial and spiritual well-being. The objective of the study is to identify the impact of financial management on young families within the framework of Islamic consumption. The problem formulation involves a general overview of the financial challenges faced by young families and the importance of implementing Islamic principles. The research aims to analyze financial challenges, explore Islamic principles, and develop effective strategies in the financial management of young families. This article is a literature review utilizing qualitative methods. Document data is collected from relevant journals and books and analyzed using content analysis methods. The research findings indicate that financial management within the framework of Islamic consumption has a positive impact. Young families actively applying Islamic principles experience improved financial well-being, spiritual balance, and a positive contribution to society through business practices and investments aligned with Sharia principles